The association between maternal diabetes and the risk of attention deficit hyperactivity disorder in offspring: an updated systematic review and meta-analysis. - Damtie, Yitayish; Dachew, Berihun Assefa; Ayano, Getinet; Tadesse, Abay Woday; Betts, Kim; Alati, Rosa (European Child & Adolescent Psychiatry, 2025)
Mixed results have been reported regarding the link between different types of maternal diabetes and attention deficit hyperactivity disorder (ADHD) in offspring. Hence, we conducted a systematic review and meta-analysis to explore these associations. Relevant studies on the subject were retrieved from six major databases, including PubMed, Medline, Embase, Scopus, CINAHL, and PsychINFO. The methodological quality of the included studies was evaluated using the Newcastle-Ottawa Scale, and between-study heterogeneity was assessed using the I2 statistic. Subgroup, sensitivity, and meta-regression analyses were conducted to identify the sources of heterogeneity between studies. In total, seventeen observational studies (five case-control and twelve cohort studies) with 18,063,336 study participants were included in the final analysis. Our random-effects meta-analysis revealed that exposure to any form of maternal diabetes was associated with an increased risk of ADHD in children. Specifically, we observed a heightened risk of ADHD in children exposed to gestational diabetes mellitus, any pre-existing diabetes, pre-existing type 1 diabetes mellitus, and type 2 diabetes mellitus. Our study suggests that children exposed to diabetes during prenatal development are at a higher risk of developing ADHD. These findings underscore the critical importance of early screening and timely interventions for exposed offspring.